Data Analysis and Background Subtraction in Neutron Spin Echo Spectroscopy - Hoffmann, Ingo (Frontiers in Physics, 2021)
With the constantly improving performance of neutron spin echo (NSE) spectrometers it becomes possible to perform measurements on increasingly complex samples and to study more and more delicate effects. To properly study such effects, proper background correction becomes increasingly import. In this paper, we will review different methods to subtract the buffer from NSE measurements and study the effect of small errors in the subtraction of the background. In the large dynamic range of modern neutron spin-echo spectrometers multiple effects become visible in a single measurement. Specifically, for vesicles both membrane undulations and translational diffusion have an effect on the intermediate scattering function in the NSE time window and here, we will investigate how taking this into account differently affects the results obtained from data analysis.